Caveolin-1 and -2 and their relationship to cerebral amyloid angiopathy in Alzheimer's disease. - van Helmond, Z; Miners, J; Bednall, E; Chalmers, K; Zhang, Y; Wilcock, G; Love, S; Kehoe, P (2007)
Cerebral amyloid angiopathy (CAA) affects over 90% of patients with Alzheimer's disease (AD) and increases the risk of cerebral haemorrhage and infarction. Caveolae--cholesterol-enriched plasmalemmal microinvaginations--are implicated in the production of amyloid beta peptide (Abeta). Caveolin-1 (CAV-1) is essential for the formation of caveolae. Caveolin-2 (CAV-2) is expressed at the plasma membrane only when in a stable hetero-oligomeric complex with CAV-1. CAV-1 and CAV-2 are highly co-expressed by endothelium and smooth muscle. Recent studies suggest that down-regulation of CAV-1 causes a reduction in alpha-secretase activity and consequent accumulation of Abeta. We have used quantitative immunohistochemical techniques to assess the relationship between CAV-1 and CAV-2 with respect to Abeta accumulation in the cerebral vasculature in a series of post mortem brains. CAV-1 and CAV-2 were co-expressed within the tunica media and endothelium of cerebral blood vessels. There were regional differences in CAV-1 immunolabelling, which was significantly greater in the frontal cortex and white matter than in the parietal lobe (in both control and AD cases) or the temporal lobe (in AD alone). However, CAV-1 labelling in AD did not differ from that in controls in any of the three lobes examined. Assessment of CAV-1 labelling in relation to the severity of CAA showed CAV-1 to be significantly increased in the frontal white matter in a subgroup of AD cases with absent/mild CAA compared with controls with absent/mild CAA and to AD cases with moderate/severe CAA, but the latter groups did not show significant differences from one another. CAV-1 labelling did not vary with age, gender, APOE genotype, post mortem delay or brain weight. Only segments of blood vessels with particularly abundant Abeta and extensive loss of smooth muscle actin showed loss of CAV-1 and CAV-2 from the tunica media. Within these vessels endothelial CAV-1 was preserved and discontinuous CAV-2 labelling was noted along the outer aspect of the vessel wall. Our findings suggest that alterations in the expression of vascular CAV-1 and CAV-2 are unlikely to play a role in the development of CAA in AD.